Mortar Dating Methodology: Assessing Recurrent Issues and Needs for Further Research. Issue 6 (28th December 2017) - Hayen, Roald; Van Strydonck, Mark; Fontaine, Laurent; Boudin, Mathieu; Lindroos, Alf; Heinemeier, Jan; Ringbom, Åsa; Michalska, Danuta; Hajdas, Irka; Hueglin, Sophie; Marzaioli, Fabio; Terrasi, Filippo; et al.
Abstract: Absolute dating of mortars is crucial when trying to pin down construction phases of archaeological sites and historic stone buildings to a certain point in time or to confirm, but possibly also challenge, existing chronologies. To evaluate various sample preparation methods for radiocarbon ( 14 C) dating of mortars as well as to compare different dating methods, i.e. 14 C and optically stimulated luminescence (OSL), a mortar dating intercomparison study (MODIS) was set up, exploring existing limits and needs for further research. Four mortar samples were selected and distributed among the participating laboratories: one of which was expected not to present any problem related to the sample preparation methodologies for anthropogenic lime extraction, whereas all others addressed specific known sample preparation issues. Data obtained from the various mortar dating approaches are evaluated relative to the historical framework of the mortar samples and any deviation observed is contextualized to the composition and specific mineralogy of the sampled material.